Novel Biomarkers in Membranous Nephropathy - Liu, Qiuying; Liu, Jianhua; Lin, Baoxu; Zhang, Yue; Ma, Meichen; Yang, Mei; Qin, Xiaosong (Frontiers in Immunology, 2022)
Membranous nephropathy (MN) is the main cause of adult nephrotic syndrome. The pathogenesis of MN is complex and involves subepithelial immune complex deposition. Approximately one-third of patients with MN develop end-stage renal disease. Timely diagnosis and reasonable intervention are the keys to improving prognosis. In recent years, with the development of high-throughput technologies, such as mass spectrometry, microarray, and sequencing technologies, the discovery of biomarkers for MN has become an important area of research. In this review, we summarize the significant progress in biomarker identification. For example, a variety of podocyte target antigens and their autoantibodies have been reported. Phospholipase A2 receptor(PLA2R) is the most well-established target antigen in MN. PLA2R and its autoantibodies have clinical significance, with both diagnostic and therapeutic value for MN. In addition, a variety of new biomarkers, including proteins, metabolites, noncoding RNAs, and immune cells, have recently been found. These MN-related biomarkers have great significance in the diagnosis, monitoring, and prediction of treatment outcomes and prognosis in MN.